128k views
5 votes
0.4x - 2.5 = 1.3x + 4.7

User Virullius
by
5.7k points

2 Answers

2 votes

Answer:

x=-8

Explanation:

Step 1.) 0.4x-2.5=1.3x+4.7

Step 2.) -2.5=1.3x-0.4x+4.7

Step 3.) -2.5=0.9x+4.7

Step 4.) -2.5-4.7=0.9x

Step 5.) -7.2=0.9x

Step 6.) -7.2/0.9=x

Step 7.) -8=x

User Wakachamo
by
4.9k points
1 vote
Simplifying
0.4x + -2.5 = 1.3x + 4.7

Reorder the terms:
-2.5 + 0.4x = 1.3x + 4.7

Reorder the terms:
-2.5 + 0.4x = 4.7 + 1.3x

Solving
-2.5 + 0.4x = 4.7 + 1.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.3x' to each side of the equation.
-2.5 + 0.4x + -1.3x = 4.7 + 1.3x + -1.3x

Combine like terms: 0.4x + -1.3x = -0.9x
-2.5 + -0.9x = 4.7 + 1.3x + -1.3x

Combine like terms: 1.3x + -1.3x = 0.0
-2.5 + -0.9x = 4.7 + 0.0
-2.5 + -0.9x = 4.7

Add '2.5' to each side of the equation.
-2.5 + 2.5 + -0.9x = 4.7 + 2.5

Combine like terms: -2.5 + 2.5 = 0.0
0.0 + -0.9x = 4.7 + 2.5
-0.9x = 4.7 + 2.5

Combine like terms: 4.7 + 2.5 = 7.2
-0.9x = 7.2

Divide each side by '-0.9'.
x = -8

Simplifying
x = -8
User Meklarian
by
4.8k points